Life Cycle Assessment and Activity-Based Costing for Low-Cost Aluminum die manufacturing: A comparative study of machining process, conventional and rapid investment casting - Samina Bibi; Muhammad Sajid; Wasim Ahmad; Muhammad Asad Ali; Mirza Jahanzaib; Salman Hussain (Results in Engineering)
Aluminum die manufacturing plays a critical role in various industrial applications, but traditional production methods such as machining process (MP) and conventional investment casting (CIC) are often associated with high energy consumption, extended cycle times, and substantial environmental impacts. With increasing global emphasis on sustainable manufacturing, rapid investment casting (RIC) has emerged as a promising alternative, leveraging additive manufacturing to improve efficiency and reduce ecological burdens. This study conducts a comparative life cycle assessment (LCA) of MP, CIC, and RIC, evaluating their impact on production time, cost, energy usage, and carbon emissions. A gate-to-gate system boundary was adopted for the LCA, focusing exclusively on internal production processes from material input to the completion of the aluminum mold. The environmental assessment is based on real-world production data and carried out using OpenLCA version 2.30, employing the CML-IA baseline v2.18 method to ensure standardized impact quantification. In parallel, Activity-Based Costing (ABC) is utilized to analyze the detailed cost structure of each process. ABC results indicate that CIC incurs the highest total cost (PKR 422,600.35), with labor alone contributing 81.39 %. MP follows with PKR 330,252.70, while RIC demonstrates the lowest cost (PKR 124,685.50) and more balanced cost distribution, with labor accounting for just 60.47 %. LCA findings further position RIC as the most sustainable option, recording the lowest global warming potential (3.56865e+2 kg CO₂-eq), fossil fuel depletion (4.31693e+3 MJ), and acidification (1.78031 kg SO₂-eq). While MP outperforms CIC environmentally in some areas, it is hindered by high energy use and material waste. In addition to quantifying the comparative performance of the three processes, this study addresses key research gaps, including the lack of integrated environmental and economic evaluations of aluminum die manufacturing routes, insufficient analysis of process-level trade-offs among time, cost, and emissions, and the limited use of real-world production data in previous assessments.